PENERAPAN STANDAR PEMBIAYAAN PENDIDIKAN INKLUSIF SEBAGAI DASAR PENYUSUNAN ANGGARAN PADA SD PANTARA TEBET JAKARTA - Hartanti Hartanti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
Inclusive education is an education for children with special needs in lieu of regular school or public. SD pantara an inclusive education institutions, in carrying out teaching and learning activities necessary infrastructure facilities. Those facilities tailored to the needs of each educational institution organized in standard financing. The standard is used as the basis for budget preparation. This study used a qualitative descriptive analysis technique where the standard of education in elementary pantara financing include labor standards, standards of facilities and infrastructure, and supporting standards are used as the basis for the preparation of the Budget and the academic year 2013/2014 2012/2013.  The results of his research is the education budget has increased compared 2013/2014 2012/2013 the budget year in terms of revenue, labor standards, standards of facilities and infrastructure, backup. While supporting existing standards decline over the previous year, due to the contribution of donors, thereby reducing the expenses of supporting standards. Keyword : budget, financing, inclusive education